Side-chain manipulation on accepting units of two-dimensional benzo[1, 2-b:4, 5-b′]dithiophene polymers for organic photovoltaics. Issue 7 (21st January 2016) - Xu, Zhongsheng; Luo, Guoping; Yu, Jiangsheng; Yin, Xinxing; Zhu, Enwei; Zhang, Fujun; Wu, Hongbin; Tang, Weihua
Abstract : Two donor–acceptor alternating polymers of bis(octylthio)thienyl BDT and fluorinated BT or 5-dodecylthienyl-6-fluorobenzo[ c ][1, 2, 5]thiadiazole were designed for organic photovoltaics. Abstract : Two donor–acceptor alternating polymers of bis(octylthio)thienyl benzo[1, 2- b :4, 5- b ′]dithiophene (BDTTs) and fluorinated benzo[ c ][1, 2, 5]thiadiazole (fBT) or 5-dodecylthienyl-6-fluorobenzo[ c ][1, 2, 5]thiadiazole were designed for organic photovoltaic applications. The polymers displayed strong absorptions in the range of 300–650 nm and bandgaps of ∼1.60 eV. Bulk-heterojunction solar cells ofPBDTTs-fBT and (6, 6)-phenyl C71 -butyric acid methyl ester (PC71 BM) blends exhibited a maximum power conversion efficiency of 6.27%. Experimental results and theoretical modelling were correlated to reveal the impact of substitution on fluorinated BT on the optoelectronic properties of the resulting polymers.